2018
DOI: 10.3389/fimmu.2018.00299
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α Subtypes As an Adjunct Therapeutic Approach for Human Immunodeficiency Virus Functional Cure

Abstract: Human immunodeficiency virus (HIV) establishes life-long latency in infected individuals. Although highly active antiretroviral therapy (HAART) has had a significant impact on the course of HIV infection leading to a better long-term outcome, the pool of latent reservoir remains substantial even under HAART. Numerous approaches have been under development with the goal of eradicating the latent HIV reservoir though with limited success. Approaches that combine immune-mediated control of HIV to activate both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 93 publications
0
18
1
Order By: Relevance
“…There were no correlation between plasma viral loads and either Tfh cells or Bcl6 expression on B cells suggesting that the changes we observed may be likely related to the local LN microenvironment. It is possible that Type I IFN may play a role as some studies have suggested and elevated levels of IFNα have been reported in the LN during SIV and HIV infections . Additional studies are needed to delineate these changes in detail and to determine the consequences they have for immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no correlation between plasma viral loads and either Tfh cells or Bcl6 expression on B cells suggesting that the changes we observed may be likely related to the local LN microenvironment. It is possible that Type I IFN may play a role as some studies have suggested and elevated levels of IFNα have been reported in the LN during SIV and HIV infections . Additional studies are needed to delineate these changes in detail and to determine the consequences they have for immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…22 We observed similar contrasting phenotypes in chronically infected rhesus macaques with significantly higher frequencies of Bcl6 + IgG + 26,27 and elevated levels of IFNα have been reported in the LN during SIV and HIV infections. 28,29 Additional studies are needed to delineate these changes in detail and to determine the consequences they have for immune responses. Early treatment with reverse transcriptase inhibitors significantly suppresses peak plasma IFNalpha in vivo during acute simian immunodeficiency virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlighted IFNα as a potential adjunct to an HIV-1 curative strategy [6][7][8][9][10]. However, almost all HIV-1 clinical trials with IFNα were performed with only one subtype, IFNα2, with mixed results (reviewed in [2,3]).…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing ambiguity regarding the IFN-α subtypes’ functional role (reviewed in reference 28) spurred us to reexamine whether these 12 highly similar cytokines, which all trigger the same JAK/STAT signaling pathway, can genuinely induce differential activities or whether our understanding of the IFN-α subtypes’ intrinsic properties has been masked by dose-related effects. To this end, we investigated the antiviral properties of IFN-α subtypes in ex vivo HIV-infected primary cells with a focus on assessing the dose-dependent effects of a selected set of IFN-α subtypes.…”
Section: Introductionmentioning
confidence: 99%